Afganistano Goro provincijos archeologijos paveldas ir jo apsaugos problemos - Luchtanas, Aleksiejus (Lietuvos istorijos studijos, 2010)
Heritage of the Ghor province has not been protected and is still being devastated by long years of war actions. Archaeological researches have almost never been made in Ghor province of Afghanistan. Therefore, a lot of archaeological monuments have never been localized and still are damaged by human actions or by nature, influenced by natural erosion. Lithuanian archaeological expedition in the province of Ghor is a constituent part of the long-term program "Archaeological - heritage mission in Ghor province, Afghanistan, 2007-2010". This program is dedicated to the preservation and registering of the archaeological heritage of Ghor province in Afghanistan. Within the distance of 60 km from the centre of province Chaghcharan, archaeological sites of value were visited and registered. Register certificates were started for 11 archaeological sites discovered in autumn 2007 as well as for 9 ones found in spring 2008.Ghor province is full of easily recognizable objects of archaeological heritage:• Ancient settlements (tapa), which have chronology from Eneolithic and Bronze Age to the Islamic period of the Middle Ages;• Remains of castles and fortresses from the 1st millennium A.D.;• Monuments from Buddhistic period - monastery of Vayguna Sange Bar (first half of the 15th millennium);• Remains of settlements and cult objects of Kabre Zabok;• Monuments of technology and engineering - mills, brickyards, ruins of bridges, caravanserais - still exist in many places.One of the aims of the archaeological - heritage project is training local heritage specialists to use modern technologies for the registering cultural valuables and for the heritage preservation purposes. During researches, damage made to the cultural valuables and possible dangers are analyzed. Recommendations about their protection are given as well. The Register of archaeological monuments in Ghor province that has been started by Lithuanian archaeologists is yet the one and only in Afghanistan.